Designing interiors - Kilmer, Rosemary; Kilmer, W. Otie (Hoboken, New Jersey John Wiley & Sons, 2024)
"Highly acclaimed, Designing Interiors opened up the world of interior design for a generation of professionals. This revised and updated Third Edition ushers in a new era of design for a new generation of interior designer students. Designing Interiors, Third Edition, provides vital information on post pandemic design trends, additional coverage of sustainability, and key issues related to building codes. Design professors Rosemary and Otie Kilmer provide a complete design history that incorporates non-Western design and dynamic color illustrations that flesh out technical concepts"--
Includes index.
Keywords: Interior decoration; Sustainable design